1993
DOI: 10.1029/92gb02793
|View full text |Cite
|
Sign up to set email alerts
|

A compilation of inventories of emissions to the atmosphere

Abstract: Detailed and accurate emissions inventories are essential for reliable computer dispersion model simulation of the behavior of chemically and radiatively important atmospheric species. Currently, model simulations of the atmosphere are limited by the paucity of quality emissions data for input. As a first step in providing internationally recognized emissions inventories, we list here the inventories that are extant, together with their spatial and temporal characteristics and a few interpretive comments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 115 publications
0
56
0
2
Order By: Relevance
“…Emissions from biomass burning are determined on a monthly basis according to the satellite-derived carbon emission estimates from the Global Fire Emissions Data base (GFED) version 2.1 (Randerson et al, 2007). NO x emissions from soils are based on Global Emissions Inventory Activity (GEIA) (Graedel et al, 1993), which are reported as monthly means. NO x emissions over Asia were obtained from Regional Emission inventory in Asia (REAS) version 1.1 (Ohara et al, 2007) The monthly/yearly emission data were linearly interpolated at each time step of the CHASER and used in the simulation.…”
Section: A Global Chemical Transport Model Chasermentioning
confidence: 99%
“…Emissions from biomass burning are determined on a monthly basis according to the satellite-derived carbon emission estimates from the Global Fire Emissions Data base (GFED) version 2.1 (Randerson et al, 2007). NO x emissions from soils are based on Global Emissions Inventory Activity (GEIA) (Graedel et al, 1993), which are reported as monthly means. NO x emissions over Asia were obtained from Regional Emission inventory in Asia (REAS) version 1.1 (Ohara et al, 2007) The monthly/yearly emission data were linearly interpolated at each time step of the CHASER and used in the simulation.…”
Section: A Global Chemical Transport Model Chasermentioning
confidence: 99%
“…The monthly biogenic emissions from vegetation, obtained via the GEIA inventory (Guenther et al, 1995), are considered for isoprene, terpenes, and other non-methane VOCs. NO x emissions from soils are based on monthly mean Global Emissions Inventory Activity (GEIA) (Graedel et al, 1993). The emissions over Asia were obtained from Regional Emission inventory in Asia (REAS) version 1.1 (Ohara et al, 2007).…”
Section: The Global Chemical Transport Model Chasermentioning
confidence: 99%
“…The emissions of the primary pollutants consist of data from the Global Emission Inventory Activity (GEIA) (Graedel et al, 1993), the Emission Database for Global Atmospheric Research (EDGAR) (Olivier et al, 1996) both with 1 • ×1 • spatial resolution and finally data from the European Monitoring Evaluation Programme (EMEP) (Vestreng, 2001) for Europe with a 50 km×50 km resolution. All emission data are provided as annual values.…”
Section: Emep Measuring Networkmentioning
confidence: 99%